Interspeech 2018 2018
DOI: 10.21437/interspeech.2018-1556
|View full text |Cite
|
Sign up to set email alerts
|

Pitch Characteristics of L2 English Speech by Chinese Speakers: A Large-scale Study

Abstract: AI-powered English learning apps are used by hundreds of millions of people across the globe on a daily basis. This presents a great opportunity for the study of L2 speech. On one hand, the amount of data accessible for research is very large and rapidly growing; on the other hand, new theories and understanding of L2 speech can be continually tested and revised through real-life and real-time applications. This paper presents a study of pitch characteristics of L2 English speech using a large-scale dataset fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In the present study, we found that compared to Spanish L1 speakers, Chinese learners tended to use higher pitch level (specifically higher minimum and mean F0), narrower span and less variable pitch in the L2. These results are in agreement with other preliminary studies on L2 speech which also documented a compressed pitch pattern for L2 speakers of different language backgrounds, and reported a similar trend towards improvement as their L2 experience increased (Busà & Urbani, 2011;Mennen, Schaeffler, & Docherty, 2009;Mennen, 1998;Peters, 2019;Shi, Zhang, & Xie, 2014;Ullakonoja, 2007;Urbani, 2012;Yuan et al, 2018;Zimmerer et al, 2014). As for the differences of F0 height, the higher pitch level observed in L2 intonation has been explained as a result of an increased cognitive effort when speaking a non-dominant language (Zimmerer et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we found that compared to Spanish L1 speakers, Chinese learners tended to use higher pitch level (specifically higher minimum and mean F0), narrower span and less variable pitch in the L2. These results are in agreement with other preliminary studies on L2 speech which also documented a compressed pitch pattern for L2 speakers of different language backgrounds, and reported a similar trend towards improvement as their L2 experience increased (Busà & Urbani, 2011;Mennen, Schaeffler, & Docherty, 2009;Mennen, 1998;Peters, 2019;Shi, Zhang, & Xie, 2014;Ullakonoja, 2007;Urbani, 2012;Yuan et al, 2018;Zimmerer et al, 2014). As for the differences of F0 height, the higher pitch level observed in L2 intonation has been explained as a result of an increased cognitive effort when speaking a non-dominant language (Zimmerer et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The factor which accounts for these differences between L1 and L2 is mainly correlated with learners' unfamiliarity and lack of knowledge of rules in producing the final-syllable stressed words, particularly when they appear in the sentence-final position that requires compressed pitch movements. In such circumstances, learners may pay more attention to the pronunciation of words and reduce the use of F0 strategies in the L2 (Mennen, Schaeffler, & Dickie, 2014;Peters, 2019;Yuan et al, 2018;Zimmerer et al, 2014). Finally, with regard to gender effects, our results are congruent with previous findings which report that women use significantly higher pitch level and greater pitch variation than men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, importantly, several studies have found that some deviated use of pitch is common in L2 speech, revealing itself as a consistent development trajectory during the L2 speech-learning process. For example, the results in previous literature (i.e., Busà & Urbani, 2011;Chen, 1972;Mennen, Schaeffler, & Dickie, 2014;Shi et al, 2014;Ullakonoja, 2007;Yuan et al, 2018) suggest that foreign speakers, regardless of their L1-L2 backgrounds, are often characterized by a narrower F0 range and less variable pitch when producing the L2 speech on the utterance level. In contrast, on the phonemic level, Chinese L2 speakers were reported to have a wider pitch span and smaller F0 fluctuations than native English speakers, mostly due to the negative attachment of L1 lexical tones to stressed syllables in the L2 (Ding et al, 2016;J.…”
Section: Introductionmentioning
confidence: 95%
“…Particularly in the domain of tone languages, only few studies have examined the acquisition of L2 intonation by L1 speakers of a tone language (He et al, 2012;Yuan et al, 2018;Liu and Reed, 2021;Shang and Elvira-García, 2022). These studies revealed effects of L2 proficiency and cross-linguistic differences, but very few studies have provided direct comparisons between learners whose L1 is a tone language versus learners whose L1 is a non-tone language.…”
Section: Introductionmentioning
confidence: 99%